PROSES BERPIKIR SISWA TUNA GRAHITA RINGAN DALAM MENYELESAIKAN MASALAH BILANGAN BULAT POSITIF BERDASARKAN TEORI ASIMILASI AKOMODASI - Lady Agustina (Prodi Pendidikan Matematika FKIP Universitas Madura, 2021)
Students with low mental disabilities have limitations in intellectual matters and have difficulty in learning the addition and subtraction of integers 1-50. The purpose of this study was to describe the thought process of low mentally disabled students in solving integer and subtraction problems associated with media use that students often encounter through observation. The thought process referred to refers to the Piaget stage indicator, namely the occurrence of disequilibrium, assimilation, or accommodation. This type of research is qualitative descriptive. The subjects in this study were two students with low mental disabilities in class V MI Al Kawtsar Panti Jember, East Java, Indonesia. The stages in this study are 1. giving questions, 2. determining trends according to theory and 3. interviewing. Both subjects cannot understand the sentence in the question and answer the question inconsistently. In addition, the two subjects were only silent when they did not know the purpose of the researchers' questions about understanding the questions. Subjects experience assimilation when the subject can immediately answer questions from the researcher spontaneously regardless of the correct or correct answer. The two subjects also experienced accommodation when they paused for a moment before answering correctly the questions from the researcher. So that the tendency of low mentally disabled students to solve the addition and reduction problems of integers is to experience the three stages of thinking according to Piaget even though that is done with a maximum approach from a researcher.